Homozygous mutation of OCLN gene in Pseudo-TORCH Syndrome Type I : A Case Report (Bangladesh Journal of Child Health, 2024)
Clinical similarities of TORCH syndrome but serological negative findings for an infectious agent named it Pseudo-TORCH syndrome, which follows autosomal recessive inheritance but it has genetic heterogeneity. Here we reported a case of 11 month old girl of consanguineous parent with psychomotor retardation, microcephaly and intracranial calcifications but she was serologically negative for TORCH infection and positive for homozygous mutation in the gene encoding occluding (OCLN) on chromosome 5.BANGLADESH J CHILD HEALTH 2022; VOL 46 (2) : 95-97